2020
DOI: 10.5194/nhess-2020-122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are Kenya Meteorological Department heavy rainfall advisories useful for forecast-based early action and early preparedness?

Abstract: Abstract. Preparedness saves lives. Forecasts can help improve preparedness by triggering early actions as part of a pre-defined protocols under the Forecast-based Action/Finance (FbA) approach, however it is essential to understand the skill of a forecast before using it as a trigger. In order to support the development of early action protocols over Kenya we evaluate the 33 heavy rainfall advisories (HRA) issued by the Kenya Meteorological Department (KMD) during 2015–2019. The majority of HRA warn c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…People are unlikely to engage in the actions necessary to protect themselves from heavy rains if they do not receive, attend to, or understand information provided by KMD. Up-to-date, researchers who are interested in public responses to weather and climate information have D focused most of their efforts on the factors that influence communication reception and understanding (Macleod et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…People are unlikely to engage in the actions necessary to protect themselves from heavy rains if they do not receive, attend to, or understand information provided by KMD. Up-to-date, researchers who are interested in public responses to weather and climate information have D focused most of their efforts on the factors that influence communication reception and understanding (Macleod et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Trigger thresholds can be determined using several methods, as noted in the scholarly literature (Coughlan de Lopez et al 2020). This study has shown that these thresholds can be further varied based on context-specific information such as crop calendars and livestock sale schedules to improve the targeting of anticipatory actions, for example, by adjusting the threshold so alerts for low-magnitude floods are triggered only during critical times of the years when lowcost interventions can be initiated through existing disaster management structures (MacLeod et al 2021).…”
mentioning
confidence: 99%